2022
DOI: 10.1111/php.13727
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen's Potential Role as aNonoxidativeFacilitator of Disulfide S–S Bond Rotation

Abstract: The role of singlet oxygen potentially mediating increased conformational flexibility of a disulfide was investigated. Density functional theory (DFT) calculations indicate that the singlet oxygenation of 1,2‐dimethyldisulfane produces a peroxy intermediate. This intermediate adopts a structure with a longer S–S bond distance and a more planar torsional angle θ (C–S–S–C) compared with the nonoxygenated 1,2‐dimethyldisulfane. The lengthened S–S bond enables a facile rotation about the torsional angle in the sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Next, we show that H-abstraction by O2 arises in an intramolecular reaction with a transition state barrier of 6.7 kcal/mol in an exothermic process to reach allene hydroperoxide 6 . Notably, peroxy intermediates arise in other 1 O 2 oxidation reactions, such as R 2 S + OO – persulfoxide, and have been implicated in the lowering of rotational energy barriers. Similarly, allene hydroperoxides and hydroxides have been previously reported in 1 O 2 oxidation of diene and trienes, and are structurally reminiscent of allene hydroxides. The protonation and hydration reactions suggest a zwitterionic form of the peroxy intermediate rather than a diradical formation. We note that Li and Smith have reported that long-term storage of indocyanine green under low-intensity light leads to oxidative dimer formation, likely via radical intermediates formed by electron transfer to form superoxide, dimerization, and the subsequent hydrogen-atom abstraction reaction.…”
Section: Resultsmentioning
confidence: 95%
“…Next, we show that H-abstraction by O2 arises in an intramolecular reaction with a transition state barrier of 6.7 kcal/mol in an exothermic process to reach allene hydroperoxide 6 . Notably, peroxy intermediates arise in other 1 O 2 oxidation reactions, such as R 2 S + OO – persulfoxide, and have been implicated in the lowering of rotational energy barriers. Similarly, allene hydroperoxides and hydroxides have been previously reported in 1 O 2 oxidation of diene and trienes, and are structurally reminiscent of allene hydroxides. The protonation and hydration reactions suggest a zwitterionic form of the peroxy intermediate rather than a diradical formation. We note that Li and Smith have reported that long-term storage of indocyanine green under low-intensity light leads to oxidative dimer formation, likely via radical intermediates formed by electron transfer to form superoxide, dimerization, and the subsequent hydrogen-atom abstraction reaction.…”
Section: Resultsmentioning
confidence: 95%
“…We conducted DFT calculations using Gaussian-16, 27 in which compounds were optimized with M06-2X/6-31G(d,p) in the gas phase in a similar manner as reported recently. 28 Unrestricted M06-2X/6-31G(d,p) calculations were conducted for the peroxyl radical and 3 O 2 , where the latter value incorporated the experimentally known singlet-triplet energy value of 22.5 kcal/mol, which was added to this calculated value of 3 O 2 . Harmonic vibrational frequency calculations were also carried out on the stationary points on the potential energy surface (PES).…”
Section: Theoretical Sectionmentioning
confidence: 99%